Theoretical model for defining seismic energy - Delipetrov, Todor; Doneva, Blagica; Delipetrev, Marjan (Geologica Macedonica, 2014)
The paper presents theoretical aspect in defining the energy of certain earthquake. The energy, as a physical quantity, is basic parameter with strong influence on all other characteristics of the earthquake. Because of the complex earthquake process, processes in the focus, as well as propagation of seismic waves in the ground, small number of researchers deals with space modeling of the earthquake. Larger is the number of those which, based on the numerous studied earthquakes, determined empirical formulas for determination of seismic energy, usually as a magnitude of a given earthquake. Given theoretical model can be a good base for defining the model of certain seismic area. Defining such type of model requires deeper knowledge of several scientific disciplines, with detailed studying of the seismic regime and geology of the terrain. Key words: seismicity; energy; model; earthquake